Urban transformations and rail stations system - the study case of Naples - Enrica Papa (European Regional Science Association (ERSA), 2005)
The paper proposes an interpretation of the physical and functional transformations, as consequences of a new metro system construction in a metropolitan area. In particolar the research, which is part of the PhD thesis work, is focused on the analysis, finalized to the transformations management, of the activities and the spaces autorganizzazione phenomena in the new metro station areas. The paper describes the approach, the research methodology utilized and the application testing in the Naples Council where a new railway network has been developed. The first results provide a methodology for the interpretation of the impacts of the new station on the urban system and a GIS decision support tools for the managment of the urban system transformation process.
Keywords: 330